Interaction of europium and curium with alpha-amylase. Issue 21 (11th February 2016) - Barkleit, Astrid; Heller, Anne; Ikeda-Ohno, Atsushi; Bernhard, Gert
Abstract : Batch sorption experiments, potentiometric and spectroscopic titration investigations revealed a fast and strong interaction of Eu(iii ) and Cm(iii ) with the digestive enzyme α-amylase. Abstract : The complexation of Eu(iii ) and Cm(iii ) with the protein α-amylase (Amy), a major enzyme in saliva and pancreatic juice, was investigated over wide ranges of pH and concentration at both ambient and physiological temperatures. Macroscopic sorption experiments demonstrated a strong and fast binding of Eu(iii ) to Amy between pH 5 and 8. The protein provides three independent, non-cooperative binding sites for Eu(iii ). The overall association constant of these three binding sites on the protein was calculated to be log  K = 6.4 ± 0.1 at ambient temperature. With potentiometric titration, the averaged deprotonation constant of the carboxyl groups (the aspartic and glutamic acid residues) of Amy was determined to be p K a = 5.23 ± 0.14 at 25 °C and 5.11 ± 0.24 at 37 °C. Time-resolved laser-induced fluorescence spectroscopy (TRLFS) revealed two different species for both Eu(iii ) and Cm(iii ) with Amy. In the case of the Eu(iii ) species, the stability constants were determined to be log  β 11 = 4.7 ± 0.2 and log  β 13 = 12.0 ± 0.4 for Eu : Amy = 1 : 1 and 1 : 3 complexes, respectively, whereas the values for the respective Cm(iii ) species were log  β 11 = 4.8 ± 0.1 and log  β 13 = 12.1 ± 0.1. Furthermore, the obtained stability constants were extrapolated to infinite dilution to make our data compatible with the existing thermodynamic database.